Rancang Bangun CCTV berbasis Wireless Sensor Network dengan Sistem Deteksi Pergerakan untuk Keamanan Rumah - Wahyu Pria Purnama; Rakhmadhany Primananda; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Home security system is an important and mandatory thing that must be considered by every homeowner. Therefore, one solution that is widely used is to use CCTV to monitor the state of the home environment, but the current CCTV data stored is in the form of video which usually requires a large enough storage space of course it is less efficient in the use of storage space. The solution is to build a CCTV with a system that uses image files as a data format, in addition to more efficient storage of image data formats, it also makes the system work less so that it is lower power than video formats. Therefore in this research, a CCTV system based on Wireless Sensor Network with Motion Detection System for Home Security consists of 3 sensor nodes and a sink node. When the sensor node detects a movement of the system will send a notification to the homeowner and take pictures automatically then send it to the sink node. Homeowners will receive a URL address to access the image file. This system communicates using a WiFi network and consists of several components, namely: 3 ESP32 microcontrollers and a camera, 3 SR501 PIR (Passive InfraRed) sensors and a Raspberry Pi Model B. Based on the results of trials on this system it was found that the system can detect movement by effective in the range of 1 meter to 6 meters from moving objects. Each sensor node is able to send images to the sink node. The system is able to send notifications to homeowners and the system can provide a URL address so that image files can be accessed remotely.